DRD3 Ser9Gly polymorphism and treatment response to antipsychotics in schizophrenia: A meta-analysis. (24th August 2022) - Liu, Chuanyong; Xu, Xiaohong; Liu, Xiaoyan; Zhang, Teng; Li, Yaoyao; Yan, Pan
Highlights: Clarify the impact of DRD3 Ser9Gly polymorphism on APDs response in SCZ. The Ser9Gly polymorphism was significantly associated with APDs response. Ser allele and Ser/Ser genotype contributed to poor APDs response in Caucasians. Abstract: The association between dopamine D3 receptor (DRD3) Ser9Gly polymorphism and treatment response to antipsychotic drugs (APDs) in schizophrenia (SCZ) has been widely reported with inconsistent results, thus we performed an updated meta-analysis to derive a more precise estimation of the relationship. PubMed, Cochrane Library, Medline, Embase, CNKI, Weipu and Wanfang databases were searched for eligible studies published until March 2022. Odds ratios (ORs) with 95 % confidence intervals (CIs) were used to assess the strength of the associations in four genetic models. A total of 13 studies with 1769 patients were included in this meta-analysis. Our findings suggested that Ser9Gly polymorphism was significantly associated with treatment response to APDs in SCZ in allele model (Ser vs Gly, OR = 0.72, 95 % CI = 0.58–0.89, P = 0.002), recessive model (Ser/Ser vs Ser/Gly + Gly/Gly, OR = 0.55, 95 % CI = 0.36–0.86, P = 0.008) and co-dominant model (Ser/Ser vs Gly/Gly, OR = 0.57, 95 % CI = 0.33–0.99, P = 0.045) in Caucasians, but not in Asians. meta-regression revealed that the associations were not confounded by mean age, male ratio and treatment duration ( P > 0.05). In summary, our results indicated the DRD3 Ser9Gly may influence the efficacy of APDs in specific genetic models, of which Ser allele and Ser/Ser genotype contributed to poor treatment response in Caucasians.